Exciton-polaritons in multilayer WSe2 in a planar microcavity. (22nd October 2019) - Król, Mateusz; Rechcińska, Katarzyna; Nogajewski, Karol; Grzeszczyk, Magdalena; Łempicka, Karolina; Mirek, Rafał; Piotrowska, Sara; Watanabe, Kenji; Taniguchi, Takashi; Molas, Maciej R; Potemski, Marek; Szczytko, Jacek; et al.
Abstract: Due to high binding energy and oscillator strength, excitons in thin flakes of transition metal dichalcogenides constitute a perfect foundation for realizing a strongly coupled light-matter system. In this paper we investigate mono- and few-layer WSe2 flakes encapsulated in hexagonal boron nitride and incorporated into a planar dielectric cavity. We use an open cavity design which provides tunability of the cavity mode energy by as much as 150 meV. We observe a strong coupling regime between the cavity photons and the neutral excitons in direct-bandgap monolayer WSe2, as well as in few-layer WSe2 flakes exhibiting indirect bandgap. We discuss the dependence of the exciton's oscillator strength and resonance linewidth on the number of layers and predict the exciton–photon coupling strength.